Comparison of microwave-assisted induction heating system (MAIH) and individual heating methods on the quality of pre-packaged white shrimp. (October 2021) - Tsai, Yung-Hsiang; Hwang, Chiu-Chu; Lin, Chung-Saint; Lin, Chih-Ying; Ou, Tsung-Yin; Chang, Tien-Hsiang; Lee, Yi-Chen
Abstract: Microwave-assisted induction heating (MAIH) is a novel heating technology that combines microwave heating in the upper section and induction heating at the bottom. Our previous study demonstrated that optimal cooking in white shrimp can be achieved by MAIH either at 130 °C for 80 s or at 90 °C for 100 s. The objective of this study was to compare the cooking of white shrimp using microwave heating or induction heating alone with that using MAIH under the optimum cooking condition. The following three methods for cooking white shrimp were analyzed: (1) induction heating (IH) at 90 °C for 100 s or at 130 °C for 80 s; (2) microwave heating (MW) at 1300 W and 2450 MHz for 80 or 100 s; and (3) MAIH at 90 °C for 100 s or at 130 °C for 80 s. The results showed that using only induction or microwave heating gave the shrimp an uncooked or undercooked appearance; meanwhile, cold spots and non-uniform temperature distribution were observed in the thermal image of the shrimp. On the contrary, the shrimps processed by MAIH were found to be fully cooked, and a uniform temperature distribution was observed in the corresponding thermal image. Furthermore, no detectable aerobic plate count (APC), psychrophilic bacteria count (PBC), and coliform were found in the shrimp samples processed by MAIH. The color ( L*, a*, b*, W, and ΔE ), hardness, cohesiveness and chewiness of the samples processed by MAIH were all significantly greater ( p  < 0.05) than those of shrimp processed by induction or microwave heating alone, indicating that MAIH cooking shrimp exhibited better color and texture than MW or IH alone. The results showed that the shrimps heated with MAIH at both 130 °C or 90 °C had better microbiological, physical and chemical quality, as compared to MW or IH heating alone. Industrial relevance: This novel MAIH technology allows shrimp to be heated and pasteurized after being packed, thereby eliminating the post-pollution issue. Therefore, it has a great potential for developing short-time in-package pasteurization processes in food industry. Highlights: Undercooked shrimp was observed after MW (80 s or 100 s) or IH (90 °C/100 s or 130 °C/80 s) heating alone. MAIH (130 °C/80 s or 90 °C/100 s) was an effective method to make pasteurization on pre-packaged shrimp. MAIH cooking shrimp exhibited better color and texture than those with MW or IH alone. MAIH system is a novel and simple equipment for shrimp cooking and pasteurization simultaneously.